Penguatan Bisnis Digital Berbasis Ekonomi Hijau bagi Pengembangan UMKM Desa Suka Indah Kabupaten Serang - Arianto, Bambang; Rani, Rani (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The purpose of community service is to encourage micro, small, and medium enterprises in Suka Indah Village to adapt to digital business and the concept of a green economy. The digitalization era requires MSME activists to be able to transform with various digital means and also actively pay attention to aspects of the green economy so that MSME activists can be environmentally friendly. In community service in Suka Indah Village, Baros, Serang Regency, which was held on 12th August 2024, assistance was provided in creating digital business tools, such as social media and e-commerce accounts, and how to operate them. The implementation method includes training and assistance. In the training, various knowledge of digital business techniques and green economy concepts was provided for the development of MSME businesses in rural areas. The success of this activity can be seen from the increasing knowledge and understanding of MSME activists in Suka Indah Village about the use of digital business through social media. MSME activists in Suka Indah Village are also able to operate businesses based on the green economy concept.